Secretory Vesicles Targeted to Plasma Membrane During Pollen Germination and Tube Growth - Ruan, Huaqiang; Li, Jiang; Wang, Ting; Ren, Haiyun (Frontiers in Cell and Developmental Biology, 2021)
Pollen germination and pollen tube growth are important biological events in the sexual reproduction of higher plants, during which a large number of vesicle trafficking and membrane fusion events occur. When secretory vesicles are transported via the F-actin network in proximity to the apex of the pollen tube, the secretory vesicles are tethered and fused to the plasma membrane by tethering factors and SNARE proteins, respectively. The coupling and uncoupling between the vesicle membrane and plasma membrane are also regulated by dynamic cytoskeleton, proteins, and signaling molecules, including small G proteins, calcium, and PIP2. In this review, we focus on the current knowledge regarding secretory vesicle delivery, tethering, and fusion during pollen germination and tube growth and summarize the progress in research on how regulators and signaling molecules participate in the above processes.